Search for neutral weakly interacting massive particles in the Fermilab Tevatron wideband neutrino beam. - Gallas, E; Abolins, M; Brock, R; Cobau, W; Hatcher, R; Owen, D; Perkins, G; Tartaglia, M; Weerts, H; Bogert, D; Fuess, S; Koizumi, G; et al. (1995)
A time-of-flight technique has been used to search for neutral weakly interacting massive particles in the wideband neutrino beam at the Fermilab Tevatron. Limits at the 90% confidence level are reported herein for (a) heavy neutrino production from the decay of heavy quark states, (b) massive objects directly produced in 800 GeV/c pN interactions that are noninteracting but unstable with a mean lifetime between 10-8 and 10-4 s, and (c) directly produced massive objects that are stable but weakly interacting with interaction cross sections between 10-29 and 10-31 cm2. © 1995 The American Physical Society.